Antiques foe [large type] - Allan, Barbara (Allan, Barbara. Trash 'n' treasures mystery., 2024)
"When popular podcaster Nicole Chatterton wants an interview for Killers Caught, true-crime author Vivian Borne is overjoyed. Finally, some recognition for the sleuthing skills the septuagenarian antiques dealer and her daughter Brandy have demonstrated, solving countless crimes in their small hometown of Serenity, Iowa! Dolled up and dressed to the nines, Vivian figures the interview is going swimmingly . . . until Nicole turns the tables, accusing the mother/daughter duo of committing the very crimes they solved. Shocked and affronted - and with a spiteful tirade captured by the cameras - Vivian breaks off the interview, ejecting the rude podcaster from the premises of the Trash 'n' Treasures shop. How dare the woman? Later, when Vivian pays the podcaster a follow-up visit at the woman's hotel - hoping to smooth things out and set the record straight - a very dead Nicole is waiting. Caught as the killer (true to the podcast's title) by producer Clare Shields, Vivian finds herself behind bars. Now it's up to Brandy to determine who really did the dire deed before their fiendish foe can strike again!"--